2019
DOI: 10.1130/g46159.1
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic aliasing and the transient nature of deep-water depositional sequences: Revisiting the Mississippi Fan

Abstract: Sequence stratigraphy remains the foremost methodology used to describe the stratigraphic record and to interpret the controls on deposition; yet, it relies on long-standing assumptions that few studies have sought to validate. Here, we present results from testing hypotheses related to the deep-water depositional sequence model by revisiting the seismic-based type locality: the Mississippi Fan, in the central Gulf of Mexico. By independently testing the relationship between cycles of relative sea-level change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similar studies have been undertaken in geospatial research such as Konkol et al (2019) who demonstrated technical issues with spatial statistics results they reproduced from several papers. In addition to these, targeted studies focusing on specific type localities which inform many of our subsurface models, such as Madof et al (2019) reassessment of the Mississippi Fan sequences should be encouraged.…”
Section: Future Workmentioning
confidence: 99%
“…Similar studies have been undertaken in geospatial research such as Konkol et al (2019) who demonstrated technical issues with spatial statistics results they reproduced from several papers. In addition to these, targeted studies focusing on specific type localities which inform many of our subsurface models, such as Madof et al (2019) reassessment of the Mississippi Fan sequences should be encouraged.…”
Section: Future Workmentioning
confidence: 99%
“…Nevertheless, coarse-grained deep-marine deposition during high sea level may occur at a local level (1) along narrow shelves of tectonically active margins 12 15 ; (2) if shelf-penetrating canyons intersect the shoreline 12 14 , 16 ; (3) during episodes of exceptionally voluminous sediment supply 15 , 17 , 18 ; and (4) via other factors such as turbidite initiation by shelf undercurrents, longshore drift, orbital forcing, subglacial meltwater, and monsoons 13 , 19 , 20 . Despite such exceptions, and some debate about the general applicability of sequence stratigraphy 21 , the prevailing paradigm predicts minimal development of sand-rich deep-water systems along passive margins during high sea level. To test this hypothesis, we look to one of the most notable periods of elevated eustatic sea level of the Cenozoic: the warm early Eocene interval 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Testing of and modification to this model soon ensued (e.g., Hunt & Tucker 1992), and alternative models/interpretations (Helland-Hansen & Gjelbeg 1994) arose. Madof et al (2019) revisited one of the type locations (the Mississippi Fan) to re-evaluate the original models, concluding that sequence stratigraphy presents an oversimplification and called into question the concepts of accommodation-driven reciprocal sedimentation. This is not to say that the ideas within sequence stratigraphy are not useful, in fact they have been extremely important for hydrocarbon exploration.…”
Section: Introductionmentioning
confidence: 99%